The Effectiveness of Different Fossil Preparation Methods for Fossil Shrimp from The Crato Formation, Araripe Basin - Barros, Olga Alcântara (Anuário do Instituto de Geociências, 2025)
This research presents the mechanical and chemical preparation techniques of a shrimp fossil from the Crato Formation, Araripe Basin. The mechanical preparation used precision tools to remove the rock matrix, whereas the chemical preparation applied acetic acid contained in vinegar to selectively dissolve the carbonate matrix and preserve the morphological details. Ultraviolet light revealed structures that were not visible under conventional light, and detailed scientific illustrations helped document diagnostic features. The integration of these methods ensured structural preservation and enhanced the taxonomic and paleoecological understanding of the sample. This study provides a methodological basis for future research on invertebrates in the Araripe Basin.